CLASS ACTION WARGA NEGARA TERHADAP PEMERINTAH - Shofyan Hasan (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2014)
Indonesia is a country that embraced the principles of democracy, and respect, the sovereignty of the people. As a consequence the implementation of these democratic principles, every five years the Democratic Party that is implemented elections. In the study of democracy, there is a postulations that almost always be confirmed in the empirical field, that a country has achieved democracy has consolidated when through three times in a democratic election, after the collapse of the authoritarian New Order regime of Indonesia had to do it. This article will discuss more deeply about the rights of citizens to sue the government in a class action.ملخص: اندونيسيا هي البلد الذي اعتنق مبادئ الديمقراطية، واحترام، وسيادة الشعب. نتيجة لتنفيذ هذه المبادئ الديمقراطية، ومرة كل خمس سنوات للحزب الديمقراطي التي يتم تنفيذها الانتخابات. في دراسة للديمقراطية، وهناك مسلمات أن يكون دائما تقريبا أكدت في الميدان التجريبي، أن البلد قد حقق الديمقراطية الموحدة عندما عبر ثلاث مرات في انتخابات ديمقراطية، وبعد انهيار النظام الشمولي من النظام الجديد يتعين على اندونيسيا نفعل ذلك. هذه المادة وسوف يناقش أكثر عمقا حول حقوق المواطنين في مقاضاة الحكومة في الطبقة العمل.